Kewenangan Penyelidikan Kasus Korupsi di Tubuh TNI: Siapa yang Berhak? - Dina Maliah Hasan; Muh. Akbar Fhad Syahril; Muhammad Tahir; Hasdar Hasdar; Murdiono Murdiono (Jurnal Litigasi Amsir, 2024)
The handling of corruption cases within the Indonesian National Army (TNI) faces significant challenges related to the overlap of authority between the Corruption Eradication Commission (KPK) and the military judiciary. Based on Undang-Undang Nomor 31 Tahun 1997 tentang Peradilan Militer and Undang-Undang Nomor 30 Tahun 2002 tentang KPK, there are differences in jurisdiction that often cause conflicts in the handling of corruption cases involving members of the TNI. This study analyzes relevant regulations and underlying legal theories, and identifies the need for harmonization of laws and regulations, capacity building of law enforcement officials, and better coordination between law enforcement agencies. With a comprehensive and sustainable approach, it is hoped that the criminal justice system in Indonesia can function more effectively and provide fairer justice for all parties involved.